1984
DOI: 10.1128/aac.25.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Common beta-lactamase-specifying plasmid in Haemophilus ducreyi and Neisseria gonorrhoeae

Abstract: Eighty-nine strains of Haemophilus ducreyi from a chancroid epidemic in Orange County, California, were examined for plasmid content. Seventy-eight (88%) of these isolates were found to contain a plasmid of 3.2 megadaltons which conferred P-lactamase production. Restriction endonuclease digests indicated that this was the same plasmid that was found in some strains of ,-lactamase-producing Neisseria gonorrhoeae.Plasmids of 5.7 and 7.0 megadaltons (MD) mediating ampicillin resistance in Haemophilus ducreyi have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Plasmid-mediated b-lactamase production is well described [11], and H. ducreyi is considered inherently resistant to both tetracyclines and penicillin [12]. However, none of these isolates contained a b-lactamase; 1 patient who received penicillin responded well.…”
mentioning
confidence: 99%
“…Plasmid-mediated b-lactamase production is well described [11], and H. ducreyi is considered inherently resistant to both tetracyclines and penicillin [12]. However, none of these isolates contained a b-lactamase; 1 patient who received penicillin responded well.…”
mentioning
confidence: 99%
“…However, Southern blot analysis confirmed that the three enzymes were molecularly related. Aminoglycosides Chancroid has been treated successfully with streptomycin (10,11), kanamycin (101), and gentamicin (93). In Singapore, failures following streptomycin therapy have been observed since 1980 (126), and susceptibility studies have shown that a large percentage of these strains were resistant to both streptomycin and kanamycin.…”
Section: Chloramphenicolmentioning
confidence: 99%
“…Plasmid-and chromosomally mediated antimicrobial resistance of Haemophilus ducreyi has complicated identification of optimal therapy for chancroid (1,7). Almost all strains are resistant to ampicillin by plasmid-mediated ,-lactamase production (7).…”
mentioning
confidence: 99%